Applying Unit Analysis Method to Establish Congruent Standard Parameters for Problems of Coolant Fluid. - Trinh , Văn Dũng; Nguyen , Tấn Dũng; Tran , Ngọc Hào (Journal of Technical Education Science, 2008)
The Expansion Processing is a very important process of the Refrigeration and Air Conditioning, by invention of the process the industrial refrigeration systems and the civil refrigeration systems are developed more perfect. However, this process is not studied thoroughly until now because it is such a complicated process and has so many parameters related to the process. For this reason, establishing maths models to solve problems of the process will be not easy. In this paper, we will introduce a unit analysis method to establish maths models and similar unit parameters for the Expansion processing refrigerant problems